2010
DOI: 10.1152/ajplung.00256.2009
|View full text |Cite
|
Sign up to set email alerts
|

Complete lack of vitamin C intake generates pulmonary emphysema in senescence marker protein-30 knockout mice

Abstract: Vitamin C (VC) is a potent antioxidant and plays an essential role in collagen synthesis. As we previously reported, senescence marker protein-30 (SMP30) knockout (KO) mice cannot synthesize VC due to the genetic disruption of gluconolactonase (i.e., SMP30). Here, we utilized SMP30 KO mice deprived of VC and found that VC depletion caused pulmonary emphysema due to oxidative stress and a decrease of collagen synthesis by the third month of age. We grew SMP30 KO mice and wild-type (WT) mice on VC-free chow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 51 publications
0
30
2
Order By: Relevance
“…Hence, SIRT1 activation downregulated SIPS through FOXO3/p21 pathway, thereby protecting against emphysema. In addition to FOXO3, recent studies have demonstrated the involvement of other developmental and senescence-related genes, such as Wnt/β-catenin, Notch, Klotho, senescence marker protein-30, and Werner syndrome protein, in the development of emphysema (55)(56)(57)(58)(59)(60). However, it remains to be seen whether SIRT1 targets these genes in response to CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SIRT1 activation downregulated SIPS through FOXO3/p21 pathway, thereby protecting against emphysema. In addition to FOXO3, recent studies have demonstrated the involvement of other developmental and senescence-related genes, such as Wnt/β-catenin, Notch, Klotho, senescence marker protein-30, and Werner syndrome protein, in the development of emphysema (55)(56)(57)(58)(59)(60). However, it remains to be seen whether SIRT1 targets these genes in response to CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that carbonyls/oxidants generated or present in cigarette smoke cause immunosenescence of T-and B-cells, leading to abnormal recognition of self-antigens, which is important for the development of COPD (14,54,62,90,109). The involvement of cellular senescence in the pathogenesis of emphysema is also shown in various studies using genetically altered mouse strains (55,64,108,112,139). However, the molecular mechanisms that underlie cigarette smoke-induced cellular senescence in vitro in lung cells and in vivo in mouse lung and the precise role of SIPS in the development of COPD/emphysema are unclear.…”
Section: Hdac2 Regulation In Cellular Senescencementioning
confidence: 96%
“…Some authors had reported that Vit C modulated the level of SIRT1 and played an important roles in lung development through affecting oxidant-antioxidant balance in rats [27]. Vit C also stimulated the activity of SIRT1 which deacetylated 7-amino-4-methylcoumarin-labeled acetylated peptide [28].…”
Section: Discussionmentioning
confidence: 99%